1976
DOI: 10.1128/iai.13.6.1678-1683.1976
|View full text |Cite|
|
Sign up to set email alerts
|

Rosette-forming cells during immune response to Toxoplasma gondii in mice

Abstract: The rosette-forming cell (RFC) response of mice immunized with varying doses of Toxoplasma gondii was studied by immunocytoadherence (ICA). The specificity of ICA in the present system was tested by passive sensitization with hyperimmune serum in vivo and in vitro. A slight increase in RFC was observed with the latter. Prior treatment of spleen cells from immunized animals with rabbit anti-mouse immunoglobulin resulted in total inhibition of ICA. During the primary and the secondary response after 10 days, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In an earlier study from our laboratory, animals immunized for 24 h with formalin-treated toxoplasma demonstrated an increase in the number of antigen-binding cells as detected by the rosette formation of tachyzoites around the splenocytes [13]. Depletion of adherent cells from the spleen suspension showed that a considerable proportion of the total rosettes was formed by the adherent cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study from our laboratory, animals immunized for 24 h with formalin-treated toxoplasma demonstrated an increase in the number of antigen-binding cells as detected by the rosette formation of tachyzoites around the splenocytes [13]. Depletion of adherent cells from the spleen suspension showed that a considerable proportion of the total rosettes was formed by the adherent cells [14].…”
Section: Discussionmentioning
confidence: 99%